Prevalence and Pattern of Congenital Anomalies in a Tertiary Hospital in Central Vietnam. (4th August 2019) - Giang, Hoang Thi Nam; Bechtold-Dalla Pozza, Susanne; Ulrich, Sarah; Linh, Le Khac; Tran, Hoang Thi
Abstract: Background: Burden and pattern of congenital anomalies are insufficiently reported in Vietnam. This study aims to determine the prevalence and pattern of congenital anomalies in neonates in a tertiary hospital in central Vietnam. Methods: A prospective cross-sectional study recruited all newborns with congenital anomalies in Da Nang Hospital for Women and Children—where nearly 60% neonates in the city are delivered. Results: Over a 1-year period, 551 out of 14 335 registered live births were found to have congenital anomalies, equivalent to an overall prevalence of 384.4 per 10 000 live births. Congenital heart defects were the most common type (52.3%) with the prevalence of 200.9 per 10 000 live births, followed by anomalies of musculoskeletal system, digestive system. Conclusions: This study revealed a high prevalence of congenital anomalies with the most common type being congenital heart defects in central Vietnam compared to both higher income countries and resource-limited settings.